Photogrammetry: Dwelling amongst the Artefacts (Architecture Image Studies, 2025)
This paper explores the ontology of photogrammetry beyond its role as an analytical process to accurately record places. It identifies photogrammetric scans as hybrid artefacts, which can capture a wide array of spatial and temporal information upon their surfaces. Such traces are explored through the work of Object Oriented Ontology philosopher Timothy Morton, with cues also taken from the work of John Ruskin who places emphasis on the stained surface as the site of a building’s value. Presented alongside these propositions are a series of photogrammetric studies where antagonistic and disruptive data is maintained in the outcome to allow the manifestation of these concealed relationships. The awareness of these syncopated chronologies questions the futurity of a recorded object, accommodating both its presence and absence. What is argued here can allow the scan to become a site for speculation and proposition beyond the deferral to a real-world object.Author Biography Cameron Stebbing, Architectural Designer, Donald Insall Associates YorkCameron Setbbing is an architectural designer at Donald Insall Associates and a visiting lecturer at Leeds Beckett University. Completing his MArch at the University of Huddersfield in 2023, he received the RIBA Silver and Dissertation Medals nominations and RIBA for his thesis project, which explored themes of conservation and temporality structured around Ruskin’s ‘The Seven Lamps of Architecture’. Portions of this were subsequently published in AD magazine in 2024. He was named RIBA East Midlands Student of the Year in 2019 and received the RIBA Bronze Medal nomination for his undergraduate work at the University of Lincoln.